Vanillyl alcohol oxidase from Diplodia corticola: Residues Ala420 and Glu466 allow for efficient catalysis of syringyl derivatives - Eggerichs, Daniel (2023)
Vanillyl alcohol oxidases (VAOs) belong to the 4-phenol oxidases family and are found predominantly in lignin-degrading ascomycetes. Systematical investigation of the enzyme family at the sequence level resulted in discovery and characterization of the second recombinantly produced VAO member, DcVAO, from Diplodia corticola. Remarkably high activities for 2,6-substituted substrates like 4-allyl-2,6-dimethoxy-phenol (3.5 ± 0.02 U mg−1) or 4-(hydroxymethyl)-2,6-dimethoxyphenol (6.3 ± 0.5 U mg−1) were observed, which could be attributed to a Phe to Ala exchange in the catalytic center. In order to rationalize this rare substrate preference among VAOs, we resurrected and characterized three ancestral enzymes and performed mutagenesis analyses. The results indicate that a Cys/Glu exchange was required to retain activity for ɣ-hydroxylations and shifted the acceptance towards benzyl ethers (up to 4.0 ± 0.1 U mg−1). Our findings contribute to the understanding of the functionality of VAO enzyme group, and with DcVAO, we add a new enzyme to the repertoire of ether cleaving biocatalysts.